2020
DOI: 10.1097/md.0000000000020491
|View full text |Cite
|
Sign up to set email alerts
|

Atypical polypoid adenomyoma follow-up and management

Abstract: Background: Atypical polypoid adenomyoma (APA) is a rare uterine tumor typically found in fertile age and associated with infertility. Among young nullipara women, conservative treatment is proposed despite the high recurrence rate and the association with endometrial cancer. Our aim was to assess the risk of recurrence with different conservative treatments in fertile ages and the prevalence of malignant or pre-malignant associated lesions to better address an adequate patient counsell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…44,45 APA is associated with an increased risk of progression to endometrioid adenocarcinoma. [46][47][48] APA have molecular features similar to AH and low-grade endometrioid adenocarcinoma 44 with frequent CTNNB1 (β-catenin) mutations. 49 PMP is another rare endometrial polypoid lesion composed of complex mucinous glands with characteristic intraluminal papillary tufts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 APA is associated with an increased risk of progression to endometrioid adenocarcinoma. [46][47][48] APA have molecular features similar to AH and low-grade endometrioid adenocarcinoma 44 with frequent CTNNB1 (β-catenin) mutations. 49 PMP is another rare endometrial polypoid lesion composed of complex mucinous glands with characteristic intraluminal papillary tufts.…”
Section: Discussionmentioning
confidence: 99%
“…Morules are almost always present 44,45 . APA is associated with an increased risk of progression to endometrioid adenocarcinoma 46–48 . APA have molecular features similar to AH and low-grade endometrioid adenocarcinoma 44 with frequent CTNNB1 (β-catenin) mutations 49 .…”
Section: Discussionmentioning
confidence: 99%
“…APA is characterized by atypical architecturally complex endometrial glands within benign myomatous or fibromyomatous stroma, often accompanied by morules [ 94 , 95 ]. Despite its initial classification as a benign lesion, subsequent research has revealed an association with an elevated risk of progressing to endometrial adenocarcinoma [ 96 , 97 , 98 ]. PMP consists of irregular or complex mucinous glands displaying distinctive intraluminal papillary tufts and the absence of nuclear atypia.…”
Section: Multi-marker Panels For Identifying Ah/einmentioning
confidence: 99%
“…TPAs mainly involve normal endometrial glands with interwoven smooth muscle stroma [ 5 , 6 ]. In contrast, the APAs are lesions with unspecified malignant potential due to a crowded, irregular, and complex glandular epithelium along with abundant, chaotic, and lose smooth muscle stroma, which can resemble atypical endometrial hyperplasia [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%